A case for IL-6, IL-17A, and nitric oxide in the pathophysiology of Sjögren's syndrome. (September 2016) - Benchabane, Sarah; Boudjelida, Abdelhalim; Toumi, Ryma; Belguendouz, Houda; Youinou, Pierre; Touil-Boukoffa, Chafia
Sjögren's syndrome (SS) is an autoimmune epithelitis characterized by mononuclear cell (MNC) infiltration of the lacrimal and salivary glands (SG), as well as the presence of serum autoantibodies. This condition is a growing public health concern in Algeria. Herein, we sought to determine if the levels of interleukin (IL)-6, IL-17A, and nitric oxide (NO), were correlated with the extent of MNC infiltration. The expression of inducible NO synthase (NOS2) and CD68 was measured in the SG of all patients, but not in those of the normal controls (NCs). We included 44 primary Sjögren's syndrome (pSS) patients and 15 NCs in this study; we found that the expression of NOS2 and CD68 was elevated in all of the SG of SS patients. Additionally, the serum and saliva levels of IL-6, IL-17A, and NO were higher in the pSS patients, compared with the NCs. Furthermore, the NOS2-induced excess NO was associated with the extent of the MNC infiltration, and thereby with tissue injury. It is also important to note that there were correlations between the levels of IL-6, IL-17A, and NO. Such findings indicate that through the effects of NO, IL-17A participates in the pathophysiology of the disease. With the purpose of improving both the diagnosis and prognosis, IL-6, IL-17A, and NO should be assayed in the serum and saliva of patients suspected of SS.